Food frequency questionnaire for dietary assessment among adults at a risk of coronary heart disease: A mixed‐methods study. Issue 7 (27th March 2022) - Zhang, Youjuan; Cheng, Ho Yu; Zang, Yuli; Choi, Kai Chow; Chair, Sek Ying
Abstract: Aims and objectives: To develop and psychometrically test a food frequency questionnaire for adults at risk of coronary heart disease (Cardio‐FFQ). Background: Comprehensive dietary assessment is critical for the prevention of cardiovascular disease, but appropriate instruments to perform this work are lacking. Design: A sequential mixed‐methods study followed the COREQ and STROBE guidelines. Methods: This study was conducted between April 2016 and November 2017. It started with dietary history interviews (Phase 1) to identify candidate food items of the Cardio‐FFQ, which validity and reliability were assessed (Phase 2) through expert consultation and four seasonal measurements, including test and retest with a 2‐week gap every season. Physical activity and blood glucose and lipids were assessed seasonally, while another FFQ was administered during the fourth measurement. Content analysis was used to analyse verbatim interview transcripts, while descriptive and inferential analyses were used to simplify the Cardio‐FFQ and examine its psychometric properties. Results: Phase I involved 34 participants during their first onset of acute coronary syndrome and generated 176 candidate food items (consumed by at least three participants) under 12 food categories. These food items were simplified to form the 133‐item Cardio‐FFQ after discarding items with trivial contributions to food commonalities or between‐person variance. Further analysis showed that the simplified questionnaire had satisfactory content validity, concurrent validity, convergent validity, predictive validity, known‐group validity and test–retest reliability. Conclusion: The 133‐item Cardio‐FFQ is a valid and reliable tool for a comprehensive dietary assessment appropriate for adults at risk of coronary heart disease. Relevance to clinical practice: Nurses may use the Cardio‐FFQ to conduct a dietary assessment to better support people to commit to healthy diets, aiming to reduce the risk of coronary heart disease.